Cover Image: Secondary crystallization kinetics. Issue 2 (24th March 2020) - Hay, James N.
Primary and Secondary Crystallization: Spherulites are commonly encountered in the crystallization of viscous fluids; viewed under polarized light and a ¼ wavelength quartz plate, solely to enhance the boundaries, they exhibit Maltese cross birefringence characteristic of spherical symmetry. The birefringence is interpreted as the radial growth of lamellar crystals and the growth rate is a measure of the lamellar growth. This structure is produced from an initial lamella which by continuous growth and branching develops a spherical contour. In his article e10007, James N. Hay has used spherulite growth to model the primary crystallization mechanism occurring in polymers limited by the final impingement of the spherulites. The cover image shows nucleation of the spherulites as heterogeneous with diameters of similar size. (DOI: 10.1002/PCR2.10007 )